THE CONCEPT “CHILD” IN FAIRY TALES (TAMADDUN NURI JURNALI, 2025)
This article provides information about the expression of the concept of “child” in fairy tales and its several semantic manifestations. It discusses the child’s upbringing, their place in society, and attitudes towards the child from a religious and spiritual perspective, along with a semantic and linguocultural analysis of the child concept.